Chromatin and epigenetics in all their states: Meeting report of the first conference on Epigenetic and Chromatin Regulation of Plant Traits - January 14 – 15, 2016 - Strasbourg, France. Issue 8 (2nd August 2016) - Bey, Till; Jamge, Suraj; Klemme, Sonja; Komar, Dorota Natalia; Le Gall, Sabine; Mikulski, Pawel; Schmidt, Martin; Zicola, Johan; Berr, Alexandre
ABSTRACT: In January 2016, the first Epigenetic and Chromatin Regulation of Plant Traits conference was held in Strasbourg, France. An all-star lineup of speakers, a packed audience of 130 participants from over 20 countries, and a friendly scientific atmosphere contributed to make this conference a meeting to remember. In this article we summarize some of the new insights into chromatin, epigenetics, and epigenomics research and highlight nascent ideas and emerging concepts in this exciting area of research.